Comparison of cleaning efficiency and deformation characteristics of Twisted File and ProTaper rotary instruments - Li, Hang; Zhang, Chenzheng; Li, Qing; Wang, Changning; Song, Yaling (European Journal of Dentistry, 2014)
Objective: The objective of the following study is to compare the cleaning efficiency and deformation characteristics of Twisted File (TF) and ProTaper (PT) nickel-titanium rotary instruments in root canal preparation. Materials and Methods: A total of 52 canals from 26 extracted maxillary first molars were randomly assigned into two groups of each including 13 mesiobuccal and 12 distobuccal (DB) canals. Two DB canals were as blank controls. After preparation with TF and PT, we recorded the preparation time and evaluate the amounts of debris and smear layer at apical, middle and coronal canals under scanning electron microscopy (SEM). Three cross-sections of canals at 3 mm, 5 mm and 7 mm from the apex foramens were scanned before and after preparation under micro-computed tomography. Changes of the cross-section area (CSA) at the three levels were calculated with Photoshop CS4. File deformation was also investigated under SEM. Two groups were statistically compared with Mann-Whitney test and independent sample t-test. Results: Less debris and smear layer were found in coronal regions of canals prepared with TF (P = 0.006, P = 0.001, respectively). TF group displayed more CSA change than PT group (P = 0.045) at cross-sections of 5 mm from the apex foramens and took significantly less preparation time than PT group did (P = 9.06 × 10−28). All five TF files without obvious micro-cracks and two out of 25 PT files with many micro-cracks showed visible unwound deformation. Conclusion: Neither TF nor PT achieves complete cleanliness of canal walls. Their deformation features might indicate different fracture resistance. TF single-file technique would substantially shorten the time of root canal preparation.
Keywords: Cleaning efficiency; deformation; ProTaper; Twisted File